Behaviour and morphology in wild guppies from populations with high and low predation pressure in Trinidad - Ashworth, William Harry (SLU/Dept. Of Aquatic Resources, 2020)
Behaviour and morphology can vary significantly within a species as a result of the predation pressure individuals are exposed to. Wild populations of guppies (Poecilia reticulata) exposed to high and low predation can be found in the streams of northern Trinidad, providing a useful study system for investigating how behaviour and morphology are affected by predation. In the present study, I investigated how behaviour, colouration and size in male guppies from 3 Trinidadian streams (Aripo, Tunapuna/Tacarigua, Turure) was affected by predation pressure. This was achieved by quantifying the behaviour of males from high and low predation regimes in the presence of a female conspecific from the same population. I also measured the amount of orange and black colouration on each side of the males. I found that behaviour and morphology were only affected by predation regime in guppies from one of the streams, namely Turure. Males from the high predation environment of Turure spent more time in proximity of the female conspecific, had less total black colouration, and were smaller than males from the low predation environment of the same stream. Males from Turure also had less total orange colouration, and less orange colouration symmetry than males from the other two streams (Aripo and Tunapuna/Tacarigua), regardless of predation regime. These results are interesting as the stream Turure belongs to a different drainage (Oropuche) than the streams Aripo and Tunapuna/Tacarigua (Caroni). This investigation highlights the possibility that predation regime may affect behaviour and morphology differently depending on the populations which are being studied, potentially due to significant ecological variation between drainages.